GENETIC DIVERSITY ANALYSIS AMONG MUNGBEAN GENOTYPES BASED ON RAPD MARKERS GENOTYPES BASED ON RAPD MARKERS - K. H. P. REDDY; V. SAI SRUTHI, L. SWATHI, D. M. REDDY, (The Bioscan, 2018)
The present study was done to investigate the genetic diversity among mungbean germplasm for identification of diversified parents to develop high yielding potential hybrids. Random amplified polymorphic DNA (RAPD) analysis of 40 markers was performed for twelve mungbean genotypes to study the DNA polymorphism. Amplification of genomic DNA of popular twelve genotypes with these RAPD primers yielded 58 RAPD fragments of which 37 were polymorphic, with an average of five polymorphic fragments per primer. Number of amplified fragments with random primers ranged from 10 (OPD 1) to 2 (OPD 2 &OPD 7). Percentage of polymorphism ranged from 28% (OPC 9) to 100% (OPB 1 & OPB 3) with an average of 63%. The Jaccard’s similarity values ranged from 0.385 to 0.821 and genotypes subjected to UPGMA were grouped into three clusters. Our study has established that the RAPD markers are useful for studying genetic diversity among mungbean genotypes and thereby helps in selecting diverse parents for utilization in hybridization for the recovery of superior hybrid